Exercise reshapes gut microbiota to ameliorate core symptoms in PCOS: molecular mechanisms and therapeutic implications - Li, Qianqian; Chen, Leqin; Wang, Ronghui (Frontiers in Endocrinology, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is a prevalent endocrine-metabolic disorder characterized by Insulin Resistance (IR), hyperandrogenism, and ovulatory dysfunction, with gut dysbiosis emerging as a key pathophysiological driver. Exercise, a non-pharmacological intervention, ameliorates PCOS symptoms, yet the molecular mechanisms linking exercise-induced gut microbiota remodeling to metabolic improvements remain elusive.ObjectiveThis review synthesizes evidence on how exercise reshapes gut microbiota to reverse core PCOS pathologies through integrated molecular pathways.ResultsExercise enriches beneficial taxa (e.g., Faecalibacterium, Roseburia, Akkermansia muciniphila) and reduces pro-inflammatory pathogens (e.g., Proteobacteria), elevating short-chain fatty acids (SCFAs) and secondary bile acids (BAs) while suppressing lipopolysaccharide (LPS) translocation. We propose three core mechanisms:(1) SCFAs network reconstruction: Butyrate/propionate enhance gut barrier integrity (via ZO-1/Occludin), inhibit histone deacetylases (suppressing CYP17A1), activate GLP-1 secretion (FFAR3-dependent), and mitigate inflammation. (2) BA-FXR axis activation: Exercise increases secondary BAs (e.g., deoxycholic acid), activating hepatic FXR to inhibit gluconeogenesis (*PEPCK/G6Pase*) and upregulate androgen-clearance enzymes (*SULT2A1/CYP3A4*). (3) LPS-inflammation inhibition: Reduced LPS blunts TLR4/NF-κB signaling and NLRP3 inflammasome activation, resolving chronic inflammation. These axes converge to improve tissue-specific PCOS features: ovarian androgen synthesis (HDAC/NF-κB inhibition), hepatic IR (FXR/PI3K-Akt), and ovulatory function (AhR-mediated Treg/Th17 balance). Exercise modality differentially impacts PCOS subtypes—endurance training benefits IR-dominant phenotypes via SCFAs producers, while resistance training reduces inflammation in obese PCOS.ConclusionExercise remodels the gut microbiota-metabolism-immune network to reverse PCOS pathophysiology. Targeting microbial metabolites (e.g., butyrate, BAs) or their receptors (FXR, GPR43) offers novel therapeutic strategies. Future research must address PCOS heterogeneity and optimize exercise protocols for microbiota-directed precision medicine.